Evaluation of Subchronic Oral Dose Toxicity of Freeze-Dried Skimmed Powder of Zophobas atratus Larvae (frpfdZAL) in Rats - Sun Young Kim; Kyu-Won Kwak; Eun-Sung Park; Hyung Joo Yoon; Yong-Soon Kim; Kwanho Park; Eunsun Kim; Sun-Don Kim (Foods, 2020)
Zophobas atratus (Coleoptera: Tenebrionidae), the giant mealworm beetle, is known as an edible insect containing a high protein content which may serve as new sources of human food and animal feed. However, potential toxicity and food safety analyses of Z. atratus have not been previously investigated. Therefore, in this study, we aimed to evaluate toxicity of freeze-dried skimmed powder of Z. atratus larvae (frpfdZAL), known as the super mealworm. Toxicological assessments were performed at the doses of 1250, 2500, and 5000 mg/kg/day in a 2- and a 13-week oral repeated-dose toxicity study of frpfdZAL in male and female Sprague-Dawley (SD) rats in accordance with the Organisation for Economic Co-operation and Development (OECD) guidelines and the principles of Good Laboratory Practice (GLP). No toxicological changes in clinical signs, body weights, water and food consumption, urinalysis, hematology, clinical biochemistry, gross findings, and histopathological examinations were observed. In conclusion, the no-observed-adverse-effect level (NOAEL) of frpfdZAL was 5000 mg/kg/day and target organ was not identified in both sexes of rats. In addition, frpfdZAL did not induce increases of serum ImmunoglobulinE (IgE), an identifier of allergic reactions in rats. Collectively, these results suggest that frpfdZAL is safe with no adverse effects, and able to be applied as an edible ingredient or other biological uses.